TEMPO-Functionalized Nanoporous Au Nanocomposite for the Electrochemical Detection of H2O2 - Dongxiao Wen; Qianrui Liu; Ying Cui; Huaixia Yang; Jinming Kong (International Journal of Analytical Chemistry)
A novel nanocomposite of nanoporous gold nanoparticles (np-AuNPs) functionalized with 2,2,6,6-tetramethyl-1-piperidinyloxy radical (TEMPO) was prepared; assembled carboxyl groups on gold nanoporous nanoparticles surface were combined with TEMPO by the “bridge” of carboxylate-zirconium-carboxylate chemistry. SEM images and UV-Vis spectroscopies of np-AuNPs indicated that a safe, sustainable, and simplified one-step dealloying synthesis approach is successful. The TEMPO-np-AuNPs exhibited a good performance for the electrochemical detection of H2O2 due to its higher number of electrochemical activity sites and surface area of 7.49 m2g-1 for load bigger amount of TEMPO radicals. The TEMPO-functionalized np-AuNPs have a broad pH range and shorter response time for H2O2 catalysis verified by the response of amperometric signal under different pH and time interval. A wide linear range with a detection limit of 7.8 × 10-7 M and a higher sensitivity of 110.403 μA mM-1cm-2 were obtained for detecting H2O2 at optimal conditions.